Use of the Prospective Structural Analysis to Characterize Variables of Educational Quality in Primary and Secondary Venezuelan Institution - Velasquez Lugo, Milfran (2020)
The article purpose was to characterize the educational institution considering quality management. Was applied a participatory action research design, with an interpretive hermeneutical approach. The methodological description came from the prospective structural analysis, by exploring the organization starting from the planning of activities according to the educational processes, keeping the congruence with the institutional mission and vision; exploring the management and organization related with the structure and guidelines of the corporation where the institution belongs; and recognizing control of activities and staff. The Structural analysis use MICMAC as prospective strategy. Among the findings, key variables emerge from the prospective, highlighting strategic planning in the educational institution, where human talent and performance have a high level of importance in order to organizational improvements.